Dampak Inovasi Pembelajaran Berbasis Karakter Terhadap Pengembangan Karakter Positif di SD Karakter Genius Islamic School Kota Depok - Susanto, Susanto (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
This study aims to analyze the impact of character-based learning innovation on developing positive characters in the Character Genius Islamic School Elementary School in Depok. This study uses a qualitative research approach with data collection techniques using interviews, observations, and literature review. Character-based learning innovations at the Genius Islamic School Character Elementary School are designed, developed, and structured dynamically by the teachers by prioritizing noble character values ​​based on local wisdom. The development of character-based learning at SD Character Genius Islamic School is carried out through various strategies, including implementing Seven Core Values ​​or 7 (seven) pillars of character in every learning and civilizing process in the school environment, including religious pillars, discipline, empathy, respect, integrity, critical thinking, and self-regulated learning. The various learning strategies carried out by the teachers at the Character Genius Islamic School have a positive impact on students' character development. With the highest results obtained, namely Religion Belief, with an achievement of 97%. It shows that teachers have succeeded in internalizing religious values ​​to students, informing positive characters always to hold fast and believe in their religious teachings.